Penerapan Metode Min-Max Stock untuk Efisiensi Persediaan Jumbo Bag pada PT. XYZ - Priyatna Septedi Inrianto; Rusindiyanto (Jurnal Serambi Engineering, 2025)
Efficiently managed inventory is a key element in supporting smooth operations and cost control in a company. This research aims to analyse the application of the Min-Max Stock method in the management of jumbo bag inventory at PT. XYZ, evaluate its effectiveness in reducing the risk of overstocking and out-of-stocking, and provide recommendations to improve the efficiency of inventory management. The research methodology used is descriptive quantitative with data collected from records of jumbo bag usage and purchases over a period of time. Calculations are carried out to determine safety stock, minimum stock, maximum stock and reorder point. The research results show that the application of the min-max stock method is able to optimise inventory management. With a safety stock value of 216 shares, minimum stock of 520 shares, maximum stock of 824 shares and reorder point of 520 shares. This research concludes that the Min-Max Stock method is an effective tool for managing jumbo bag inventory. Further research is recommended to explore the integration of these methods with digital technology to improve the accuracy and efficiency of inventory management systems.